PENGARUH CORPORATE SOCIAL RESPONSIBILITY, CORPORATE GOVERNANCE, LEVERAGE, DAN PROFITABILITAS TERHADAP TAX AVOIDANCE - Ayu Septiani; Dul Mu'id (Diponegoro Journal of Accounting, 2019)
The purpose of this research is to see the effect of Corporate Social Responsibility, Corporate Governance, Leverage, and Profitability on Tax Avoidance in Companies Listed on the Indonesia, Malaysia, Philippines, Thailand and Singapore Stock Exchanges period 2014-2016.The sample consists of 216 companies listed in the Indonesia, Malaysia, Philippines, Thailand and Singapore Stock Exchanges period 2014-2016. The data that was used in this research was secondary data and selected by using purposive sampling method. The analisis method that was used in this research was multiple linear regression. Before being conducted by regression test, it was examined by using the classical assumption tests.The result of this study shows that the the environmental score, social score, governance score, have positive significant influence to Tax Avoidance. Leverage have negative significant influence to Tax Avoidance. Profitablitas did not have significant influence to tax avoidance.